Natural killer T cells accelerate atherogenesis in mice - Nakai, Y; Iwabuchi, K; Fujii, S; Ishimori, N; Dashtsoodol, N; Watano, K; Mishima, T; Iwabuchi, C; Tanaka, S; Bezbradica, J; Nakayama, T; Taniguchi, M; et al. (American Society of Hematology, 2004)
We have investigated the potential role of CD1d-restricted natural killer T (NKT) cells in the development of atherosclerosis in mice. When fed an atherogenic diet (AD), NKT cell-deficient CD1d-/- mice had significantly smaller atherosclerotic lesions than AD-fed C57BL/6 (wild-type [WT]) mice. A significant reduction in atherosclerotic lesions was also demonstrated in AD-fed, low-density lipoprotein receptor-deficient (Ldlr-/-) mice reconstituted with CD1d-/- bone marrow cells compared with the lesions observed in Ldlr-/-mice reconstituted with WT marrow cells. In addition, repeated injections of α-GalCer or the related glycolipid OCH to apolipoprotein E knockout (apoE-/-) mice during the early phase of atherosclerosis significantly enlarged the lesion areas compared with mice injected with vehicle control. However, administering α-GalCer to apoE-/- mice with established lesions did not significantly increase the lesion area but considerably decreased the collagen content. Atherosclerosis development in either AD-fed WT or apoE-/- mice was associated with the presence of Vα14Jα18 transcripts in the atherosclerotic arterial walls, indicating that NKT cells were recruited to these lesions. Thioglycolate-elicited macrophages pulsed with oxidized low-density lipoproteins expressed enhanced CD1d levels and induced NKT cells to produce interferon-γ, a potentially proatherogenic T-helper 1 (TH1) cytokine. Collectively, we conclude that NKT cells are proatherogenic in mice.